The Causal Effect of Corporate Governance on Corporate Social Responsibility - Jo, Hoje; Harjoto, Maretno A. (2012)
In this article, we examine the empirical association between corporate governance (CG) and corporate social responsibility (CSR) engagement by investigating their causal effects. Employing a large and extensive US sample, we first find that while the lag of CSR does not affect CG variables, the lag of CG variables positively affects firms’ CSR engagement, after controlling for various firm characteristics. In addition, to examine the relative importance of stakeholder theory and agency theory regarding the associations among CSR, CG, and corporate financial performance (CFP), we also examine the relation between CSR and CFP. After correcting for endogeneity bias, our results show that CSR engagement positively influences CFP, supporting the conflict-resolution hypothesis based on stakeholder theory, but not the CSR overinvestment argument based on agency theory. Furthermore, firms’ CSR engagement with the community, environment, diversity, and employees plays a significantly positive role in enhancing CFP.
Keywords: Conflict Resolution; Corporate financial performance; Corporate Governance; Corporate Social Responsibility